Thirring model with jump defect - Aguirre, A. R. [UNESP]; Gomes, J. F. [UNESP]; Ymai, L. H. [UNESP]; Zimerman, A. H. [UNESP] (My University, 2009)
The purpose of our work is to extend the formulation of classical affine Toda Models in the presence of jump defects to pure fermionic Thirring model. As a first attempt we construct the Lagrangian of the Grassmanian Thirring model with jump defect (of Backlund type) and present its conserved modified momentum and energy expressions giving a first indication of its integra-bility. Copyright © owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike Licence.
Keywords: Energy expression; Lagrangian; Thirring model; Gravitation; Defects